Accessible morphohistochemical labs-on-a-chip based on different counting chambers’ grids: microfluidic morphodynamical workstations. - Gradov, O. V.; Notchenko, A. V. (Морфологія / Morphologia / Morfologìâ, 2012)
An accessible design of autonomous labs on the chip which do not require a special reader is developed. The proposed device uses hemocytometric counting chambers for determination of concentration of cells, isolated by a special device for cell sedimentation. A system of automated Rf-identification of chambers in the long-term storage is proposed which provides new morphometric data at various stages of cultivation or biomonitoring. A new diffraction method of calculation and fingerprinting of cellular structures in varying environmental conditions is described. Experimental data on the pilot testing of Fuchs-Rosenthal, Buerker, Neubauer, Makler and Thoma chambers for the described technique is given. The applicability of these devices for coherent-densitometric indication either of concentration dynamics in cell culture or suspension or morphogenetic processes in them for laminar conditions is shown. A self-learning program for cellular pattern recognition and relational cytophotometry based on lab on the chip with an object-micrometric calibration relative to the counting net is demonstrated. A hybrid in vitro / in silico method of morphogenesis monitoring in cell cultures is introduced.